Experimental investigation of fatigue crack initiation from notch for 2024 T351 Al-alloy (Fracture and Structural Integrity, 2019)
In this investigation, fatigue criterion was established to predict crack-initiation at the tip of a notch in aged hardening aluminum alloy. This criterion was used to predict the residual lifetime in aeronautical structures using concept of local stress at notch and subjected to constant amplitude loading characterized by mean stress. Charpy V-notch specimens were taken from sheet plate and the notch radius accurately machined at value of 0.2mm. The local stresses were determined numerical and validated analytically. In experimental investigation, the V-notched specimens were loaded in four point bending fatigue with a load ratio R=0.1 and variation in amplitude loading.
Keywords: Fatigue crack initiation; Notch; Finite element method; Stress field; Aluminium alloy